Exploring creative teaching strategies for teaching mechanical systems and control to grade 9 learners with special learning needs - Kekana, Katane Elizabeth (My University, 2024)
To improve the learning of learners with exceptional needs, teachers are increasingly using creative teaching tactics. Teachers that use creative teaching tactics assist learners grasp the application of basic scientific abilities as well as the acquisition of conceptual information in difficult areas such as Technology. To teach a topic like Mechanical Systems and Control, which aims to equip learners with building facility knowledge and skills using various machines including gears, belts, chains, elevators, and escalators, amongst others, it is crucial that Technology teachers know creative strategies to use to teach learners with poor concentration span and autism. The purpose of this study was to explore creative teaching strategies for teaching Mechanical Systems and Control to Grade 9 learners with special needs in the Capricorn district of Limpopo. This study used a qualitative exploratory case study design. A homogenous purposive sampling was used to select two Technology teachers from two special schools in the Capricorn district. Data was collected through non-participant observation and semi-structured interviews. This study used Shulman’s (1987) Content and Pedagogical Knowledge theory as its framework. The present research found that Technology teachers had major hurdles in identifying and use adequate creative teaching strategies to deliver Mechanical Systems and Control content to learners with special needs. These teachers could not activate their Pedagogical Content Knowledge to keep learners engaged in the lessons as some of them were learners with autism and needed creative strategies from teachers to increase their concentration span. The research revealed that even though Technology teachers used PowerPoint presentation slides, narrative discourses, textbooks, and artefacts during instruction, these strategies were not always effective for learners with special needs. This study recommended that teachers undergo a robust training on how to teach learners with special needs, focusing on the different pedagogies and methods such as the guided exploration method, technology integration, visualisation, and technological artefacts to better teach Mechanical Systems and Control concepts. These methods are learner centred and allow teachers to cater for learners’ individual learning needs.
Thesis (M. (Technology Education)) -- University of Limpopo, 2024
Keywords: Special needs; Technology; Mechanical systems and control; Creative teaching strategies; Pedagogical content knowledge; Educational technology; Teaching machines; Automatic speech recognition; Slow learning children; Pedagogical content knowledge; Creative writing (Secondary education)